Investigation of predictors for in-hospital death or long-term hospitalization in community-acquired pneumonia with risk factors for aspiration - Issei Oi; Isao Ito; Naoya Tanabe; Satoshi Konishi; Yumiko Ibi; Yu Hidaka; Nobuyoshi Hamao; Masahiro Shirata; Kensuke Nishioka; Seiichiro Imai; Yoshiro Yasutomo; Seizo Kadowaki; et al. (European Clinical Respiratory Journal)
Background It is known that the mortality of pneumonia in patients with risk factors for aspiration is worse than that in those without these risk factors. However, it is still unknown which risk factors for aspiration predict prognosis. Therefore, we aimed to determine which risk factors for aspiration are associated with death or prolonged hospitalization.Methods We prospectively followed patients with community-acquired pneumonia at a single hospital providing acute to chronic care in Japan until they died or were discharged. Patients at any risk of aspiration were included. The associations between pneumonia severity, individual risk factors for aspiration, and in-hospital death or prolonged hospitalization were investigated. Overall survival was estimated by the Kaplan – Meier method, and the factors associated with in-hospital death or prolonged hospitalization were investigated by multivariate analysis using factors selected by a stepwise method.Results In total, 765 patients with pneumonia and risk factors for aspiration were recruited. One hundred and ten patients deceased, and 259 patients were hospitalized over 27 days. In-hospital death increased as the number of risk factors for aspiration increased. In the multivariate analysis, male, impaired consciousness, acidemia, elevated blood urea nitrogen, and bedridden status before the onset of pneumonia were associated with in-hospital death (odds ratio [OR]: 2.5, 2.5, 3.6, 3.1, and 2.6; 95% confidence interval [CI]: 1.6–4.1, 1.4–4.2, 1.6–8.0, 1.9–5.0, and 1.6–4.2 respectively). In the Cox regression analysis, these factors were also associated with in-hospital death. None of the vital signs at admission were associated. Tachycardia, elevated blood urea nitrogen, hyponatremia, and bedridden status were associated with hospitalization for >27 days (OR: 4.1, 2.3, 4.3, and 2.9; 95% CI: 1.3–12.9, 1.5–3.4, 2.0–9.4, and 2.0–4.0, respectively).Conclusions Blood sampling findings and bedridden status are useful for predicting in-hospital mortality and long-term hospitalization in patients with pneumonia and any risk factor for aspiration.